Tata Kelola Pendataan dan Penyaluran BLT-DD Melalui Pasardesa.id sebagai Upaya Pencegahan Korupsi - Achidsti, Ashilly; Kafa, Muhammad Zidny; Hudani, Ahmad Mizdad (Integritas : Jurnal Antikorupsi, 2020)
This study aims to determine the implementation of BLT-DD disbursement undertaken by Pasardesa.id. This study employs a qualitative approach with case study method. Legal indicators, transparency, participation, and accountability were used to investigate the data collection management as well as the disbursement of BLT-DD through Pasardesa.id as a tool to fight against corruption. The disbursement of BLT-DD through Pasardesa.id is a policy innovation of a public service. The diversion form of direct cash transfer into balance of basic needs (sembako) potentially reduces the corruption risk. Further, the establishment of clear and transparent nature of data and BLT-DD disbursement plays a vital role in sustaining good governance. In addition, transparency and community’s participation are the key for the success of monitoring BTL-DD policy. To combat corruption, the establishment of transparent nature of data and the implementation of BLT-DD disbursement through Pasardesa.id provide greater opportunity to achieve high and measurable accountability performed by Panggungharjo Village.